Yearbook of Muslims in Europe, Volume 5. - Nielsen, Jørgen. (Yearbook of Muslims in Europe, 2013)
The Yearbook of Muslims in Europe provides an up-to-date account of the situation of Muslims in Europe. Covering 46 countries of Europe in its broader sense, the Yearbook presents a country-by-country summary of essential data with basic statistics and evaluations of their reliability, surveys of legal status and arrangements, organisations, et cetera Data have been brought up to date from the previous volume. Since 2012, the former article and review sections of the Yearbook are published as the Journal of Muslims in Europe . The Yearbook remains the annual reference work for country surveys on Muslims in Europe. The Yearbook of Muslims in Europe is an important source of reference for government and NGO officials, journalists, and policy makers as well as scholars.